A Retrospective Assessment of Return to Function in Dance after Physical Therapy for Common Dance Injuries. Issue 4 (December 2017) - Junck, Emily; Richardson, Megan; Dilgen, Faye; Liederbach, Marijeanne
An injury that causes a dancer to take time away from training or performance can be career ending, and thus it is important for dancers to have accurate expectations when considering treatment options. Thus far, few studies have reported functional outcomes after injury in dancers, which may be different than for the general athletic population. Therefore, our study sought to determine functional outcomes in dancers after operative and non-operative treatment for common dance injuries. Our outcome measures included a subjective assessment of the degree to which a dancer had returned to his or her previous level of dance, the SF-12 survey, and the WHO functional outcome scale modified for dance. We also compared these as outcome measurement tools for return to full function in dance. Secondarily, we sought to assess factors that may have contributed to poorer functional outcomes. We reviewed the charts of 675 dancers seen at our physical therapy facilities between 2006 and 2010 and identified 416 adult dancers who had experienced a dance-related injury that we categorized as "common, " based on surveys of injuries among dancers (with back injuries excluded). One hundred and sixty-four dancers completed a telephone survey about their recovery after injury. Descriptive statistics, correlation, and linear regression were then used to identify factors associated with poor functional outcomes. Sixty-three percent of the participants had a full return to their pre-injury level. No variables were found to be significantly correlated (p < 0.05) with poorer outcomes by linear regression. However, there was a trend toward better outcomes when dancers were younger, their injuries were not chronic, and their recovery was not limited by fear. The three measurement tools were all highly correlated with one another (p = 0.000) and found to be useful determinants of functional return to dance. Given that there were few strongly correlated outcome factors, we concluded that poorer functional outcomes in dance resulted from a combination of many factors, including those of a psychosocial nature. We believe these results can be used to better advise dancers who are considering treatment options, provide better estimates of possible limitations and time needed to return to dance, and potentially promote easier recoveries and better functional outcomes.